2006
DOI: 10.1007/s00431-006-0352-4
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutation in the STK11 gene in a girl with an ovarian Sertoli cell tumour

Abstract: This is the first report of a STK11 germline mutation in a girl with an ovarian Sertoli cell tumour. It remains to be shown whether this particular mutation predisposes the patient to the development of ovarian tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Sertoli cell tumours, particularly the lipid-rich and oxyphilic subtypes, have been described in children and young women with PJS 47. In the series of Oliva and colleagues, 6/54 patients with Sertoli cell tumours were reported to have PJS, of which lipid-rich and oxyphilic subtypes were predominant 44.…”
Section: Sex Cord-stromal Tumours (Scst)mentioning
confidence: 99%
“…Sertoli cell tumours, particularly the lipid-rich and oxyphilic subtypes, have been described in children and young women with PJS 47. In the series of Oliva and colleagues, 6/54 patients with Sertoli cell tumours were reported to have PJS, of which lipid-rich and oxyphilic subtypes were predominant 44.…”
Section: Sex Cord-stromal Tumours (Scst)mentioning
confidence: 99%
“…Among recorded PJS cases, more than 30% of them develop polyp-related manifestations by age 10 years and 50% by 20 years [2]. In children with PJS, intussusception due to GI polyps is the most critical symptom, while in adults, the dominant threaten are PJS-associated tumors [3]. van Lier et al [4] described cumulative intussusception risk in PJS of 15% by age 10 years and 50% by age 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…Among reported cases of PJS, more than 30% of them develop polyp-related symptoms by age 10 years and 50% by 20 years [ 2 ]. In children with PJS, intussusception due to GI polyps is the most important symptom, while PJS-associated tumors are primary in adults [ 3 ]. van Lier et al[ 4 ] reported cumulative intussusception risk in PJS of 15% by age 10 years and 50% by age 20.…”
Section: Introductionmentioning
confidence: 99%